Smell and the ancient senses - Bradley, Mark (Routledge, 2015)
From flowers and perfumes to urban sanitation and personal hygiene, smell—a sense that is simultaneously sublime and animalistic—has played a pivotal role in western culture and thought. Greek and Roman writers and thinkers lost no opportunity to connect the smells that bombarded their senses to the social, political and cultural status of the individuals and environments that they encountered: godly incense and burning sacrifices, seductive scents, aromatic cuisines, stinking bodies, pungent farmyards and festering back-streets.